Peran dan Potensi Masjid Fadhillah, Lowokwaru, Malang dalam Pembangunan Masyarakat pada Bidang Ekonomi - Barianto Nurasri Sudarmawan (Jurnal Ekonomi Akuntansi dan Manajemen, 2017)
In the time of the Prophet Muhammad, the mosque had a very central role for the community. Not only as a gathering place for ritual worship, the mosque is also used to discuss problems that occur in the community such as economic and social, and even occasionally used to formulate a strategy when the Prophet facing a war. Now days, the mosque faces a narrowing of meaning. The mosque is only used for places of worship. This study aims to explore the role and potential of mosques in Fadhillah Mosque, Lowokwaru, Malang. This mosque has a strong potential because it is supported by the trust of the community which entrust their funds and accumulate in large numbers. This study uses interviews, observation and also documentation in data mining. This research proves that the Fadhilah Mosque, Lowokwaru, Malang City does not only play a role in the aspect of ritual worship. Fadhillah Mosque is also engaged in economics through several activities. Even so, this mosque also has great potential that can still be developed to provide benefits to the wider community. Keywords: Mosque; Worship, Mosque-Based Community Empowerment